FDM 방식의 3D 프린터를 이용한 골반 골절 환자의 맞춤형 모델제작 - 오왕균(Wang-Kyun Oh) (한국콘텐츠학회 논문지, 14(11), 2014)
At present trend 3D Printing technology has been using more efficiently than conventional subtractive manufacturing method in various medical fields, in particular this technology superior in saving production time, cost and process than conventional. Especially in orthopedics, an attractive attention has been paid by adopting this technology because of improving operation, operation accuracy, and reducing the patient's pain. Though 3D printing technology has enormous applications still in some hospitals have not been using due to having the problem of technical utilization of hardware, software & chiefly financial availability and etc. In order to solve these problems by reducing the cost and time, we have used CT images in pre-operative planning by directly making the pelvic fracture model with open source DICOM viewer and STL file conversion program, assembly 3D printer of FDM wire additive manufacturing. After having the customized bone model of six patients who underwent unstable pelvic fracture surgery, we have operated our system in orthopedic section of University Hospital through the clinician. Later, we have received better reviews and comments on utilization availability, results, and precision and now our system considered to be useful in surgical planning. 최근 3D 프린팅 기술은 다양한 의학 분야에서 활용하고 있으며, 기존의 절삭가공 보다 제작시간과 비용, 과정측면에서 매우 효율적이다. 특히 정형외과에서는 수술시간, 수술 정확성 등의 개선과 환자의 고통 감소와 재수술을 최소화하는 방법으로 관심이 집중되고 있다. 그러나 기존 연구에 사용된 3D 프린터는 하드웨어 및 소프트웨어의 기술적 활용성, 재정적 가용성 등의 문제로 현재 병원에서 일반적으로 널리 사용되지 못하고 있는 실정이다. 본 연구에서는 이를 해결하기 위해 CT 영상을 Open Source DICOM Viewer와 STL 파일변환 프로그램, FDM 와이어 적층가공방식의 조립형 3D 프린터로 골반 골절 모델을 직접 제작하여 비용과 시간을 단축하고 사전 수술계획에 활용하였다. 6명의 불안정성 골반골절 수술환자의 맞춤형 골 모델을 제작한 후 대학병원 정형외과 임상의에게 골절수술 전에 제공하여 임상적 활용 가능 여부에 대한 검토와 분석의견 결과 정밀도, 해상도가 수술계획에 사용하여도 유용한 것으로 판단되었다.